AUDIOVISUAL: DO BROADCAST À BROADBAND - Kowalski, Marcio Antonio (2015)
The digital society embraces us in all of the daily aspects and a significant part of the population lives connected on multi-platforms. With the instantaneity of the communication flows, we live in a routine where many accesses are from a click or a touch away. The television as a preponderant media for many decades, in its digital transition involves a function beyond the television that we knew, as an interactive display that connects and absorbs contents from many sources. The consecrated global models of audio-visual distribution, especially by Broadcast, suffer the changes consequences of its public behavior by the new opportunities of contents acquisition, now interactive and on demand. On this context, the Smart TVs models (connected televisions) in Broadcast shows differentiated options and they require an increasing space on the connection with other displays. With this scenery, the study seeks to provide and analyze the new content offerings, applications, possibility and trends in the hybridity of the sources for the future television.